Can death be casual: the paradox in Death Café blogs - Jose A.; Singh S.; Chandra V. (My University, 2025)
Death can be a difficult matter to talk about in face-to-face conversations. However, online platforms provide a safe space for people to express feelings and opinions freely. This paper is an attempt to explore how the taboo of discussing death in a casual manner is approached by individuals in an online space. The Death Café blogs were an apt starting point for this study as the movement itself is centred on fostering casual discussions around death and its related matters. A total of 200 blogs posted on the website were studied, and the major themes were identified and analysed. By highlighting the prominent themes that emerge through a careful reading of the blogs, the study foregrounds the paradox in the assumption that liberating conversations about death and dying (as seen in the Death Café blogs and the responses) can invariably mitigate the fear of death and break the death taboo. © 2023 Informa UK Limited, trading as Taylor & Francis Group.